2006
DOI: 10.1093/intqhc/mzl028
|View full text |Cite
|
Sign up to set email alerts
|

Selecting indicators for the quality of cardiac care at the health system level in Organization for Economic Co-operation and Development countries

Abstract: The final set of 17 indicators selected by the Cardiac Care Panel constitutes a comprehensive set of measures for the most relevant domains of CV care. Nevertheless, gaps remain in the area of primary prevention and in particular in areas with rapidly changing technology and improving treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…It is noteworthy that the criteria (importance, scientific soundness, feasibility etc.) used by other studies (Idänpään-Heikkilä, 2006;Marshall et al, 2006;McLoughlin et al, 2006) to short list indicators also worked well in our setting.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is noteworthy that the criteria (importance, scientific soundness, feasibility etc.) used by other studies (Idänpään-Heikkilä, 2006;Marshall et al, 2006;McLoughlin et al, 2006) to short list indicators also worked well in our setting.…”
Section: Discussionsupporting
confidence: 52%
“…Subsequent studies can contextualize and customize BSC by each of the implementing frontline clinical units so that specialtyspecific BSCs can be developed. Other studies have also used existing documents in a similar fashion to create effective BSC (Wachtel et al, 1999;Idänpään-Heikkilä, 2006;Marshall et al, 2006;McLoughlin et al, 2006). In a recently concluded study BSC was used to track certain nursing indicators in acute care Ontario hospitals using secondary data (Hall et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the Organization for Economic Co‐operation and Development, an intergovernmental economic research institution, launched its Health Care Quality Indicators Project in 2003 (Idänpään‐Heikkilä et al. ). However, the indicators allow only national and not institutional comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this literature is usually not to present the methodology, such as the use of DELPHI or nominal-group techniques, which are widely accepted [24], but to present a final list of indicators to address a particular issue. Such articles frequently involve high-level experts that are not themselves assessed against the indicators presented [25][26][27]. However, we found that indicator development and their application should not be separated.…”
Section: Discussionmentioning
confidence: 88%